ANALISIS POTENSIAL Alpinia galanga MENGGUNAKAN JEJARING FARMAKOLOGI MELALUI ANALISIS PENGAYAAN GENE ONTOLOGY DAN KEGG (KYTO ENCYCLOPEDIA OF GENE AND GENOMES) SEBAGAI ANTIDIABETES - Fath, Dwi Hanif Muluqul; Muchlisin, Muhammad Artabah; Jamil, Ahmad Shobrun (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Alpinia galanga L., is a family of Zingiberaceae that has been used traditionally in various medicinal practices due to its therapeutic properties. With this, this research aims to identify the potential content of Alpinia galanga metabolite compounds as one of the potential alternative therapies in cases of diabetes mellitus and several other disorders. In this study, in silico methods were used, namely pharmacological networks and also Gene Ontology and KEEG pathway enrichment analysis which revealed 28 metabolite compounds that have links to plants and diseases to be studied and also revealed the enrichment of key molecular functions such as catalytic activity, protein kinase activity, and small molecule binding, indicating their regulatory and catalytic properties. In addition, KEGG (Kyto Encyclopedia of Genes and Genomes) pathway analysis highlighted its involvement in signaling pathways associated with glucose homeostasis, cancer, and hormone response. Examination of cellular component terms revealed the subcellular localization and potential interactions of A. galanga compounds in cellular compartments such as the cytoplasm, plasma membrane, and cell periphery. The results showed that out of 28 metabolite compounds, 1 metabolite compounds in A. galanga, namely 1'S-1'- acetosxychavicol, have the potential for treatment in diabetes mellitus cases and show the diverse pharmacological properties of A. galanga, which has implications for its potential in the development of new therapies targeting various diseases and disorders.